Peluang dan tantangan manajemen bank syariah Indonesia dalam menghadapi bonus demografi: indonesia - Fadhilah, Moh Nur (Maliki Interdisciplinary Journal, 2024)
The idea of a Golden Indonesia is targeted to be realized in 2045, right when Indonesia turns a century old, this discourse has attracted the attention of young people's enthusiasm to provide innovation to each other to support the success of this idea. Moreover, at the same time, Indonesia is suspected of experiencing a demographic bonus. Of course, this opportunity should not be wasted. -Just waste it, especially by the millennial generation. Indonesia's noble ideals of gold are centrally in the hands of young people. Increasing the productive percentage also means increasing economic growth in Indonesia, in this case, Islamic Bank has opportunities and challenges to realize a Golden Indonesia 2045, one of the opportunities that Bank Syari'ah will provide is the existence of several innovations in Sharia banking products, and also the challenges that Sharia Banks will experience, namely with limited capital and also weaknesses in technology and information media, one of the strategies for collaboration with other financial institutions is a strategic step in overcoming capital limitations. In this way, Sharia Banks can be better prepared to face challenges and take advantage of existing opportunities in facing the demographic bonus towards a Golden Indonesia in 2045.